OPTIMALISASI DAN STRATEGI MANAJEMEN PENGGUNAAN FACEBOOK - Vidia Anggy Christina (Jurnal Abdimas Bina Bangsa, 2023)
This study aims to find out how Facebook's strategy in beating the Tiktok platform. The study found that Facebook's decision to switch  to the metaverse  has not been right, as Facebook has not taken the opportunities that exist to innovate to grow its company. Based on other research, it also explains that Tiktok has become a prima donna substitute for Facebook for now among the public, especially generation Z. This is because Facebook remains in the comfort zone, while Tiktok takes the opportunity to attract people's attention by offering various interesting features that Facebook does not have such as music videos and filters that allow users to use it with their own creativity.  But on the other hand, Facebook tries to present features that are almost the same as Tiktok with the aim of active users returning to use applications from Facebook. Facebook, which is far behind with Tiktok, is still trying to catch up with it by remaining optimistic about its shift to the metaverse world which is  believed to help Facebook in running a sustainable company. The implication for companies that are in the comfort zone, companies need to innovate in sustainable company development because the development of the world is not always the same every year